Effect of drink temperature on antropyloroduodenal motility and gastric electrical activity in humans. Issue 3 (September 1995) - Sun, W M; Penagini, R; Hebbard, G; Malbert, C; Jones, K L; Emery, S; Dent, J; Horowitz, M
Abstract : There is little information on the motor mechanisms underlying the effects of meal temperature on gastric emptying. The effects on antropyloric pressures and the surface electrogastrogram of ingesting drinks at 4 degrees C, 37 degrees C, and 50 degrees C (350 ml normal saline and 50 ml low calorie (7 kj) orange cordial) given in randomised order were measured over 60 minutes in 12 normal volunteers (10 men and 2 women, aged 18-55 years). The warm and cold drinks suppressed antral pressure waves (p < 0.05), altered the organisation of antropyloric pressure waves (p < 0.05), stimulated isolated pyloric pressure waves (p < 0.05), and increased electrogastrogram frequency (p < 0.05) when compared with the 37 degrees C drink. These changes were greatest in the first 30 minutes after ingestion and greater (p < 0.05) with the 4 degrees C drink. Temperature has major effects on postprandial antropyloroduodenal motility in normal subjects. Both cold and warm drinks stimulate a pattern of motility associated with retardation of transpyloric flow.